Analisi Kinerja Keuangan Sebelum dan Sesudah Pandemi Covid-19 pada PT Mayora Indah Tbk (2018-2023) - Rahayu Istriyati, Atifah; Wirahadi Ahmad, Afridian (Green Publisher Indonesia, 2024)
This study aims to determine the development of the financial performance of PT Mayora Indah Tbk in 2018-2023, and whether financial performance has decreased or increased financial performance during the Covid-19 pandemic. The data collection methods used in the study were documentation and observation. The data analysis method describes descriptive quantitative with the formula for finding the level of profitability, liquidity, and solvency ratios. The results of the study in 2018-2020 financial performance increased, while after the Covid-19 pandemic in 2020-2021, financial performance experienced a very drastic decline, most likely this happened due to the impact of the Covid-19 pandemic. The influence of government policies such as the Enforcement of Restrictions on Community Activities (PPKM) implemented during the pandemic has a direct impact on companies which greatly limits economic activities, such as distribution and sales. Meanwhile, financial performance began to adjust after the 2021-2023 Covid-19 pandemic. While seen from the measurement of the solvency ratio there is no change at all, from 2018-2023 the financial ratio continues to decline. We recommend that PT Mayora Indah Tbk always improve financial resilience by building reserves to face unexpected challenges in the future.